Remote-sensing characterization of surging glaciers in High Mountain Asia in the past two decades - Ke, Linghong; Wang, Ruizhe; Zhang, Jinshan; Ding, Xin (Frontiers in Earth Science, 2024)
Glacier surge represents a special glacier behavior with abnormally high flow speeds, which can trigger catastrophic events, such as high-speed ice avalanches and glacial lake outburst floods, transforming landforms in the mountain cryosphere and impacting downstream communities. Glacier surges have been frequently observed in High Mountain Asia (HMA) in the past decades. Previous studies have been devoted to detecting and monitoring surge-type glaciers in HMA. Here we provide an updated inventory of surge-type glaciers from the literature and further extract key parameters of surge activities in HMA (active period, advance distance/rate of terminus, surging pattern, mass balance) based on time-series Landsat images and glacier surface elevation change datasets. Our inventory includes a total of 652 surge-type glaciers that surged at least once during 2000 and 2020. Surge-type glaciers exhibiting obvious spatial clustering are featured by long glacier tongues and gentle slopes. Mapping of terminus changes of 328 surge-type glaciers with clean or partly moraine-covered tongues reveal 337 surge events that occurred during the period. There are 9 glaciers exhibiting surge events twice, each lasting 2–5 years with a reoccurrence interval of ∼10 years. The length of the active period and advancing distance show a heavy-tailed distribution, with the advance rate exponentially decreasing with the extension of the active period. We identified 178 Alaska-type and 159 Svalbard-type glacier surges in HMA during the early 21st century. Glaciers in HMA are generally in a state of mass loss, but slight positive mass balance were observed in the northwestern regions where glacier surging concentrates. The differences in glacier-wide mass balance between surge-type and non-surge-type glaciers were not consistent in different subregions. Obvious glacier mass loss was observed in the post-surging period due to the transfer of glacier mass downstream with surging. The updated information on glacier surges in the HMA in the past two decades provides a basis for future glacier-related hazard monitoring and further understanding of glacier surge mechanisms in the region.